2020
DOI: 10.1371/journal.pone.0243269
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, outcomes, and the use of intensive care unit resources of critically ill patients diagnosed with COVID-19 in Sao Paulo, Brazil: A cohort study

Abstract: Background The coronavirus disease (COVID-19) pandemic has brought significant challenges worldwide, with high mortality, increased use of hospital resources, and the collapse of healthcare systems. We aimed to describe the clinical outcomes of critically ill COVID-19 patients and assess the impact on the use of hospital resources and compare with critically ill medical patients without COVID-19. Methods and findings In this retrospective cohort study, we included patients diagnosed with COVID-19 admitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 20 publications
0
18
1
3
Order By: Relevance
“…Two studies with smaller numbers of patients exclusively admitted to ICU reported a mortality of 52% in Mexico 15 and 15% in Brazil. 16 Our results indicate that, considering hospitalised patients both from the ICU and the ward, mortality in our setting may be higher than the reported in other parts of the world (12%-28%). [17][18][19][20][21] Possible reasons for the high mortality rate in this population may include differences in thresholds for hospitalisation in our country; however, the presence of high-risk factors may also be involved and is noteworthy to mention.…”
Section: Discussioncontrasting
confidence: 55%
“…Two studies with smaller numbers of patients exclusively admitted to ICU reported a mortality of 52% in Mexico 15 and 15% in Brazil. 16 Our results indicate that, considering hospitalised patients both from the ICU and the ward, mortality in our setting may be higher than the reported in other parts of the world (12%-28%). [17][18][19][20][21] Possible reasons for the high mortality rate in this population may include differences in thresholds for hospitalisation in our country; however, the presence of high-risk factors may also be involved and is noteworthy to mention.…”
Section: Discussioncontrasting
confidence: 55%
“…58 With the heterogeneous course of COVID-19, with sometimes long stays in intensive care and often septic states, appropriate control groups are mandatory. 59 Our control group was comparable with the COVID-19 cohort with regard to invasive treatments, clinical and laboratory indicators of sepsis, and general systemic inflammation. Length of hospitalization and intensive care unit stays were longer in the cohort with COVID-19, as seen elsewhere.…”
Section: Discussionmentioning
confidence: 88%
“…Patients with severe cardiovascular injury and underlying cardiac insufficiency, for example, are more likely to experience adverse events, according to recent reports ( 16 , 36 ). For clinical prognosis, summary comorbidity scales such as the CCI are widely used ( 37 , 38 ). The CCI was created to predict the probability of death within 1 year of being admitted to the hospital.…”
Section: Discussionmentioning
confidence: 99%